Identifying The Impact Of The COVID-19 Pandemic On The Indonesian Construction Sector Using The Exploratory Factor Analysis (EFA) - Cecep Kamiludin; Andreas F.V Roy (U Karst, 2022)
The COVID-19 pandemic has impacted Indonesia's construction sector. The growth of the construction sector severely declined due to the COVID-19 pandemic. However, the study of the impacts of the COVID-19 pandemic on the construction sector in Indonesia is still limited. The present study is aimed to examine the negative and positive impacts (opportunities) of the COVID-19 pandemic on the Indonesian construction sector. The study employed a quantitative approach with 128 contractors and consultants from 34 provinces in Indonesia. Through the factor analysis (EFA) and USG analysis approach, six negative and positive impacts of the COVID-19 pandemic and their priorities can be identified. The six negative impact factors are Workforce issues and Cost Overruns, Financial Performance Degradation, Project completion delays and schedule disruptions, Supply chain disruptions, Legal and contract issues, and  Difficulties in implementing health protocols and adjusting to the standard operating procedure. Meanwhile, the three positive impacts are Increasing awareness of the importance of occupational safety and health and collaboration among stakeholders, Improving the use of technology in the construction sector, and Optimizing existing procedures and systems. The study shows that the pandemic has impacted both the workforce and business entities' business Indonesian construction sector. These findings are expected to be useful in formulating strategic formulation for handling and mitigating the impact of pandemics.